Phytochemical Screening, GC-MS Profiling, and Antimicrobial Evaluation of Marigold (Tagetes erecta L.) Leaf Extract of Kathmandu, Nepal - Magar, Bhuwan Budha; Adhikari, Shreyashi; Shrestha, Ojeswi Maisaju; Thadarai, Aayush; Bhandari, Shristi; Shahi, Ikcha; Shrestha, Sabina; Pandit, Rajesh; Shrestha, Manish Man; Rai, Nelson (Journal of Nepal Chemical Society, 2026)
Tagetes erecta L. holds a significant traditional and medicinal value in Nepali culture which is locally known as “Sayapatri”. In spite of the therapeutic potential, the scientific validation of T. erecta of Nepali origin has not been properly recorded. In this work, the leaves of T. erecta was used to obtain the ethanolic extract using the Soxhlet apparatus. The leaf extract was used for preliminary phytochemical screening, which revealed the presence of essential bioactive compounds, including alkaloids, flavonoids, tannins, terpenoids, and polyphenols. For the detailed analysis, Gas Chromatography- Mass Spectroscopy (GC-MS) analysis of the extract was conducted which revealed the presence of compounds such as neophytadiene (55.42%), 9,12,15-octadecatrienoic acid (11.16%), pentadecanoic acid (10.91%), and phytol (6.72%) as major bioactive components. Further, the antimicrobial efficacy of the extract was tested against five pathogenic strains by agar-well diffusion method, two gram positive bacteria B. subtilis ATCC 6051 & S. aureus ATCC 6538P , two gram-negative bacteria E. coli ATCC 8739 & K. pneumonia ATCC 700603, and one fungal strain C. albicans ATCC 2091. The antimicrobial test results were recorded by measuring the Zone of Inhibition (ZOI) where moderate inhibitory effects of 1.1 cm was measured on E. coli, B. subtilis, S. aureus, and C. albicans, and no activity was observed against K. pneumonia. These results showcase the promising antimicrobial potential of T. erecta grown in Nepal.